Проблема «пути покаяния» в книге «Философия как путь покаяния» Танабэ Хадзимэ - Настасенко, Иван Дмитриевич (Гуманитарные исследования в Восточной Сибири и на Дальнем Востоке, 2024)
The article is devoted to the concept of «metanoetics» (zangedō), which was formulated by Tanabe Hajime in his book «Philosophy as Metanoetics» published in 1946. The author examines this work in the context of the life of the Japanese philosopher and the making of his philosophical system. The semantic content of the central concept is revealed through its connection with other concepts, such as logic, accident, freedom, etc.